The perception of medical students on the usefulness of the respiratory ventilatory augmented reality (ResVAR) application for learning the respiratory system - Saat, Azmah; O.K. Rahmat, Rahmita Wirza; Ab Razak, Nur Izah; Abas, Razif; Mohd Thani, Suryati (Penerbit Universiti Sains Malaysia, 2024)
Augmented reality (AR) is a revolutionary technology with potential educational applications. When contemplating use of AR applications in educational settings, the ease of use of the application should be considered. Here we assessed students’ perceptions regarding use of the Respiratory Ventilatory Augmented Reality (ResVAR) application in the context of learning a respiratory module. Clinical and preclinical students enrolled in the Faculty of Medicine and Health Sciences at Universiti Putra Malaysia (UPM) participated in a cross-sectional study. Study participants were first- to fifth-year medical students at UPM who were selected using a convenience sampling technique. A total of 173 participants completed a self-administered questionnaire. Data for the responses in this descriptive study were analysed using SPSS version 27. The data indicated that nearly all preclinical students (97%) and clinical students (94%) found the ResVAR are easy to use. In addition, nearly all preclinical students (98%) and most clinical students (88%) found the ResVAR are easy to read and understand. Nearly all (98% and 96% of clinical students and preclinical students, respectively) could use the application’s tools on their own and nearly all (98% of preclinical students and 99% of clinical students) said that the application helped them learn more about the respiratory system. About 88% of clinical students and 98% of preclinical students said that the ResVAR helped them better focus on the subject, and in turn they gained a better understanding and image of the respiratory system. The large majority of students (almost 96% of preclinical students and 86% of clinical students) said that the ResVAR could increase the likelihood that they would pass a test about the respiratory system. Overall, both preclinical and clinical students thought that the ResVAR was a useful teaching tool that helped them better understand the respiratory system. The findings of this study suggest that integration of the ResVAR and other similar applications and software into medical curricula could yield significant advantages for students in terms of enhanced comprehension and study of the respiratory system.